Factors Associated with Daptomycin-Induced Eosinophilic Pneumonia - Kazuhiro Ishikawa; Takahiro Matsuo; Yasumasa Tsuda; Mahbubur Rahman; Yuki Uehara; Nobuyoshi Mori (MDPI AG, 2022)
The risk factors for eosinophilic pneumonia (EP) remain unclear. We investigate the characteristics of patients with daptomycin (DAP)-induced EP and conducted a retrospective observational study. A total of 450 patients aged ≥ 18 years who received DAP (25 DAP with EP, 425 DAP without EP) were included. The median duration from the first DAP administration to EP onset was 18.0 days. Definite, probable, and possible DAP-induced EP were diagnosed in 0, 9, and 16 patients, respectively. The median age (DAP with EP, 72.0 years; DAP without EP, 64.0 years), DAP dosage/body weight (BW) (9.00 vs. 7.50 mg/kg), blood eosinophil count (cells/μL) (419 vs. 96), and the percentage of hemodialyzed patients (40.0% vs. 13.4%) were significantly higher in patients with EP than in patients without EP in the univariate analysis. In separate multivariate logistic regression analyses, age (odds ratio (OR), 1.03; 95% confidence interval (CI), 1.00-1.05), DAP dosage/BW (OR, 1.61; 95% CI, 1.25-2.07), and hemodialysis (OR, 4.42; 95% CI, 1.86-10.5) were significantly associated with DAP-induced EP. Clinicians may need to consider the potential factors associated with EP, especially in older patients, patients on hemodialysis, or patients who receive > 9.00 mg/kg of DAP.